Rumeli'nin kaybının Türk şiirindeki akisleri - (:unkn) unknown (My University, 2011)
Özet: Rumelinin kaybı Türk şiirinde önemli bir yer tutar. Asırlarca Türklerin hâkimiyetinde kalan bu toprakların kısa sürede elden çıkmasının halkı nasıl sarstığı Rıza Tevfik, Mehmet Âkif, Aka Gündüz, Arif Nihat vb. şairler tarafından şiirlerde ele alınmıştır. Özellikle Balkan Savaşları esnasında ülkeyi yönetenlerin ihmalkârlığı ve beceriksizliği bu toprakların kaybedilmesini hızlandırmasını şairler de sert bir üslûpla eleştirmiştir. Bu hususu işleyen şiirlerde dramatik bir üslûp kendisini hissettirmektedir. Yahya Kemâl, Arif Nihat, Orhan Şaik, Halide Nusret vd. şairler Rumelinin kaybının üzerinden uzun yıllar geçse de Türk halkının -özellikle Rumeli kökenli şairlerin- bu topraklara özleminin devam ettiğini ifade etmişlerdir.

Losing the land of Rumeli has had significant reflections on the Turkish poetry. Poets such as Rıza Tevfik, Mehmet Âkif, Aka Gündüz, Arif Nihat, etc. wrote poems on how much the sudden loss of Rumeli, which had long been under the Turkish rule, influenced the feelings of the Turkish people quite negatively. They harshly criticized the negligence and the incompetence of the rulers which accelerated the loss of the land during the Balkan War. One can easily observe the dramatic style in such poems. Poets such as Yahya Kemâl, Arif Nihat, Orhan Şaik, Halide Nusret have expressed that the Turkish people- and especially those poets with a Rumeli origin- will continue longing for this land, no matter how many years have passed over the loss.
Reflections of the Loss of Rumeli on the Turkish poetry
Keywords: Antropoloji